Report of Joint Study Team Eastern Districts-Uttar Pradesh - Planning Commission (Planning Commission, 1964)
With high pressure of population, frequent recurrence of floods and droughts and low productivity in agriculture, the eastern districts of Uttar Pradesh were regarded even in the Second. Five Year Plan a low-income area requiring special attention in planned economic and social development. And in .the Second and Third Five Year Plans, special allocations were made to accelerate development in these districts.
Government of India Planning Commission